2014
DOI: 10.3382/ps.2013-03703
|View full text |Cite
|
Sign up to set email alerts
|

Lysine partitioning in broiler breeders is not affected by energy or protein intake when fed at current industry levels

Abstract: A study was conducted to determine the effects of dietary energy and protein intake on the partitioning of lysine in broiler breeder hens. One hundred twenty-six broiler breeders were randomly assigned to 1 of 6 dietary treatments in a 2 (390, 450 kcal/d) × 3 (22, 24, 26 g of CP/d) fashion. Thirty-six hens were administered a daily oral dose of 15 mg of (15)N-Lys for a period of 2 wk or until first egg. After the 2-wk enrichment period, no isotopes were given for 2 d. After 2 d, a daily oral dose of 15 mg of (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
15
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 14 publications
1
15
0
Order By: Relevance
“…On the other hand, the proportion of the ND B reduced from an average 63% (balanced diet) to approximately 45% (Fig. ), corroborating with the assumption that the body protein is fundamental to provide Lys to maintaining the egg mass production (Ekmay et al., ).…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…On the other hand, the proportion of the ND B reduced from an average 63% (balanced diet) to approximately 45% (Fig. ), corroborating with the assumption that the body protein is fundamental to provide Lys to maintaining the egg mass production (Ekmay et al., ).…”
Section: Discussionsupporting
confidence: 83%
“…Lysine is an important AA for the synthesis of egg and body protein, and the absence of this AA results in lower egg production (Hiramoto et al., ). The body protein has an important role as a source of AA for egg formation (Ekmay et al., ). More recently, these authors suggested that Lys is incorporated at the rate of 78% in body protein in comparison with 22% present in the egg protein.…”
Section: Discussionmentioning
confidence: 99%
“…The metabolic pathway of lysine has been altered from muscle tissue to egg formation once broiler breeders commence their egg production, and the amount of lysine partitioned to egg formation changes according to the egg production rate [ 16 ]. In this regard, dietary lysine intake should be shortly adjusted as per hens’ age and stage of egg production, however no sufficient data on the responses to various levels of lysine in broiler breeder hens in an early-laying stage are available.…”
Section: Discussionmentioning
confidence: 99%
“…It is reasonable to assume that a relatively reduced egg production in hens offered the diet containing 0.55% and 0.59% total lysine might be partially due to decreased follicular recruitment into the F1 yolk follicle pool, evidenced by Robinson et al [ 30 ] where an increased atresia of small yellow follicles was observed when hens were unable to appropriately manage the ovarian follicles in the hierarchy. One reason for this could be due to the dietary lysine partitioning between maintenance and production was likely to be disturbed when dietary lysine was not adequate, suggested by Ekmay et al [ 16 ] found that lysine used for primarily towards muscle, and then excessive lysine utilized to egg production when needed in broiler breeder hens during the early laying period.…”
Section: Discussionmentioning
confidence: 99%
“…Chen et al (2006) described that 50 to 60% of daily ad libitum feed reduced metabolic disease, and enhanced egg quality in female broiler breeders. In this regard, commercial broiler breeder feeds are formulated with low energy and crude protein levels (Ekmay et al, 2014). For instance, when the diets contained excess lysine, it could result in a higher muscle deposition but in a lower egg production and fertility rate during laying periods (Coon, 2004).…”
Section: Introductionmentioning
confidence: 99%